Plasma proteomic signature of the risk of developing mobility disability: A 9‐year follow‐up - Osawa, Yusuke; Semba, Richard D.; Fantoni, Giovanna; Candia, Julián; Biancotto, Angélique; Tanaka, Toshiko; Bandinelli, Stefania; Ferrucci, Luigi (Aging cell, 2020)
Introduction Mobility disability is a powerful indicator of poor health in older adults. The biological and pathophysiological mechanism underlying the development of mobility disability remains unknown. This study conducted a data‐driven discovery phase investigation to identify plasma proteins that predict the incidence of mobility disability in community‐dwelling older adults without mobility disability at baseline. Methods We investigated 660 women and men, aged 71.9 ± 6.0 (60–94) years, who participated in the Invecchiare in Chianti, “Aging in the Chianti Area” study and completed the 400‐m walk at fast pace (400‐m walk) at enrollment. Median follow‐up time was 8.57 [interquartile, 3.20–9.08] years. SOMAscan technology was used to measure 1,301 plasma proteins at enrollment. The incident of mobility disability was defined as inability to complete the 400‐m walk. Protein‐specific Cox proportional hazard model was adjusted for sex, age, and other important covariates. Results Plasma levels of 75 proteins predicted mobility disability (p < .05). Significant proteins were enriched for the KEGG “PI3K‐Akt signaling,” “phagosomes,” and “cytokine–cytokine receptor interaction” pathways. After multiple comparison adjustment, plasma cathepsin S (CTSS; hazard ratio [HR] 1.33, 95% CI: 1.17, 1.51, q = 0.007), growth/differentiation factor 15 (GDF15; HR: 1.45, 95% CI: 1.23, 1.72, q = 0.007), and thrombospondin‐2 (THBS2; HR: 1.44, 95% CI: 1.22, 1.69, q = 0.007) remained significantly associated with high risk of losing mobility. Conclusion CTSS, GDF15, and THBS2 are novel blood biomarkers associated with new mobility disability in community‐dwelling individuals. Overall, our analysis suggests that cellular senescence and inflammation should be targeted for prevention of mobility disability. Among 1,301 plasma proteins assessed, cathepsin S, thrombospondin‐2, and growth/differentiation factor 15 significantly and independently predicted mobility loss in 660 community‐dwelling adults. Proteins associated with mobility loss were enriched for senescence‐associated secretory phenotype and for proteins in the PI3K‐Akt, phagosome, or cytokine–cytokine receptor interaction pathways. High plasma levels of SASP‐induced proteins related to inflammation and phagocytes activation mark a condition of high risk of mobility loss.